PEMBERDAYAAN YAYASAN IBNU DENGAN PENINGKATAN KUALITAS PAKAN AYAM KAMPUNG - Siswati, Latifa; Nizar, Rini; Azzahro, Hanifah Ulfa (Komunitas Manajemen Kompetitif, 2024)
The IBNU Foundation (Insan Berguna Nusantara) is a disability group in Pekanbaru with 500 members, most of whose members have physical disabilities. With the condition of Foundation members whose activities are limited, to earn income it is necessary to pay attention to activities to meet daily needs without too much physical activity. The IBNU Foundation has land 45m x 50 m. Part of it has been used for the Foundation's businesses, including planting chilies, cultivating fish, cultivating maggots and also raising 6 free-range chickens. The Foundation already has a chicken coop, but the number of chickens kept is still very small so the results obtained from raising chickens are also inadequate, so the chairman of the Foundation needs more chickens to increase income, from free-range chickens the benefits of chicken eggs can be sold or hatched for increase the number of chickens, if there are already a lot of chickens, they can be sold and consumed by Foundation members themselves. The problems faced by partners are: The IBNU Foundation needs a business unit that produces results quickly and does not carry out much physical activity, the number of chickens that are kept is still small, so it is necessary to improve the quality of chicken feed and assistance. Seeing the problems faced by the IBNU Foundation, Community Service activities were held by Lecturers at the Faculty of Agriculture, Lancang Kuning University with training and counseling on raising free-range chickens as well as increasing knowledge by improving the quality of free-range chicken feed raised by members of the IBNU Foundation. The methods used for this service are training and counseling to increase knowledge about free-range chicken cultivation as a source of income; Providing chicken feed; Accompaniment; Evaluation to determine understanding and increase knowledge by giving questionnaires to partners. The provision of free-range chicken feed from the Community Service Team can increase growth which will increase income and increase member activities which are positive and do not require a lot of physical activity and can be done in one location that is easy for members to reach, especially in terms of economic growth for members and the community. around the IBNU Foundation. There was an increase in knowledge of 56%. Key word : chikens,feed, IBNU foundation. Economic growth.